‘So much English by the Mother’: gender, foreigners and the mother tongue in William Haughton’s Englishmen for My Money (1598) - Smith, E (Fairleigh Dickinson University Press, 2001)
This article discusses gender and national identity in late sixteenth century London, with particular reference to Haughton's 'Englishmen for My Money'.